2023
DOI: 10.3390/w15030566
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hydrodynamic and Machine Learning Approaches for Flood Inundation Modeling

Abstract: Machine learning (also called data-driven) methods have become popular in modeling flood inundations across river basins. Among data-driven methods, traditional machine learning (ML) approaches are widely used to model flood events, and recently deep learning (DL) approaches have gained more attention across the world. In this paper, we reviewed recently published literature on ML and DL applications for flood modeling for various hydrologic and catchment characteristics. Our extensive literature review shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…It has been observed that data-driven models usually make faster predictions with minimal input using ML [47]. Multiple ML algorithms including decision tree (DT) [48], Random Forest (RF) [49] and Gradient Boost (GB) [50] have been applied to improve fault-tolerant accuracy in flood prediction handling more intricate information by applying their complex algorithms in a short time span [51]. Innovative deep learning-based model has been suggested in [52] that provides accurate and timely flood prediction as compared to traditional models.…”
Section: Related Workmentioning
confidence: 99%
“…It has been observed that data-driven models usually make faster predictions with minimal input using ML [47]. Multiple ML algorithms including decision tree (DT) [48], Random Forest (RF) [49] and Gradient Boost (GB) [50] have been applied to improve fault-tolerant accuracy in flood prediction handling more intricate information by applying their complex algorithms in a short time span [51]. Innovative deep learning-based model has been suggested in [52] that provides accurate and timely flood prediction as compared to traditional models.…”
Section: Related Workmentioning
confidence: 99%
“…Among data-driven methods, traditional machine learning (ML) approaches are widely used for inundation predictions and recently deep learning (DL) approaches have gained more attention across the research community. We reviewed recently published literature on ML and DL application for flood modelling for various hydrologic and catchment characteristics (Karim et al, 2023). Our literature review showed that DL models produce better accuracy compared to traditional approaches.…”
mentioning
confidence: 99%
“…
Scenarios of flood inundation are traditionally simulated by numerically solving the partial differential equations (PDEs) that govern fluid dynamics, with the initial and boundary conditions derived from observational data. While proven highly valuable for improving flood management and risk mitigation (Karim et al, 2023), such hydrodynamic simulations are limited in its applicability in near-real-time or emergency management due to its high demand on time and hardware resources.Drastically improved efficiency can result from leveraging the power of deep artificial neural networks (ANNs). In a recently proposed methodology known as physics-informed machine learning (PIML, Karniadakis et al, 2021), ANNs are trained to obtain numerical solutions based on the PDEs and limited observational data.
…”
mentioning
confidence: 99%
“…This category, often referred to as surrogate models, includes algorithms that predict flood inundation at specific future time points, as well as those that generate series of predictions.Compared with PIML, a key concern regarding ANN-based surrogate models is their generalizability. That is, if the simulation data used to train the surrogate model are insufficiently diverse (in terms of the covered ranges of scenarios and conditions) or inadequately representative, whether the model is able to effectively learn the underlying physics in the absence of physics-based constraints.Recently, we proposed an ANN-based framework for rapid inundation modelling in large regions (Tychsen-Smith, et al, 2023). This framework takes into account the local elevation, surface roughness, river inflows and the current water heights, and predicts the water heights at the subsequent time point.…”
mentioning
confidence: 99%
See 1 more Smart Citation